Urinary KIM-1 is not correlated with gestational age among 5-year-old children born prematurely - Restrepo, Jaime M.; Torres-Canchala, Laura; Bonventre, Joseph V.; Arias, Juan C.; Ferguson, Michael; Villegas, Adriana; Ramirez, Oscar; Filler, Guido (Frontiers in Pediatrics, 2023)
Background: Preterm birth is associated with decreased nephron endowment. Currently, there is no reliable non-invasive biomarker to identify or monitor decreased nephron number in at-risk patients. Urinary Kidney Injury Molecule-1 (KIM-1) is a biomarker of acute and chronic renal injury. We measured urinary KIM-1 among a wide array of other potential biomarkers. Methods: We conducted an ambispective cohort study of 5-years-old children born prematurely and healthy controls identified from city schools. Detailed anthropometrics, renal ultrasound dimensions, and biochemical parameters were measured. Urinary KIM-1 was measured using Luminex® technology. Age independent z-scores were calculated and compared. Spearman correlation were used for estimating the association between measures and KIM-1. Results: We enrolled 129 children, 97 (75.2%) born pre-term and 32 (24.8%) healthy controls born at full-term]. Pre-term patients had significantly lower weight and body surface area than controls. Pre-term patients and controls did not differ in current age, sex, race, height, blood pressure, urinary sodium, fractional sodium excretion, serum creatinine and estimated GFR. All spearman correlation between KIM-1 and gestational age, renal and serum measurements were weak without statistical significance Conclusion: In 5-year-old children born prematurely, KIM